Role of LAMP-2 in Lysosome Biogenesis and Autophagy - Eskelinen, Eeva-Liisa (The American Society for Cell Biology, 2002)
In LAMP-2–deficient mice autophagic vacuoles accumulate in many tissues, including liver, pancreas, muscle, and heart. Here we extend the phenotype analysis using cultured hepatocytes. In LAMP-2–deficient hepatocytes the half-life of both early and late autophagic vacuoles was prolonged as evaluated by quantitative electron microscopy. However, an endocytic tracer reached the autophagic vacuoles, indicating delivery of endo/lysosomal constituents to autophagic vacuoles. Enzyme activity measurements showed that the trafficking of some lysosomal enzymes to lysosomes was impaired. Immunoprecipitation of metabolically labeled cathepsin D indicated reduced intracellular retention and processing in the knockout cells. The steady-state level of 300-kDa mannose 6-phosphate receptor was slightly lower in LAMP-2–deficient hepatocytes, whereas that of 46-kDa mannose 6-phosphate receptor was decreased to 30% of controls due to a shorter half-life. Less receptor was found in the Golgi region and in vesicles and tubules surrounding multivesicular endosomes, suggesting impaired recycling from endosomes to the Golgi. More receptor was found in autophagic vacuoles, which may explain its shorter half-life. Our data indicate that in hepatocytes LAMP-2 deficiency either directly or indirectly leads to impaired recycling of 46-kDa mannose 6-phosphate receptors and partial mistargeting of a subset of lysosomal enzymes. Autophagic vacuoles may accumulate due to impaired capacity for lysosomal degradation.